Methicillin resistant Staphylococcus aureus isolated from meat raw in Cartagena, Colombia (2017)
To determine the prevalence of Methicillin Resistant Staphylococcus aureus (MRSA) isolated in establishments that commercialize raw ground beef and pork chops in Cartagena- Colombia. 160 samples were analyzed through microbiological cultures in Baire Parcker agar, and it was determined the presence of mecA gen that codifies the methicillin resistance and the pvl that codifies the Panton- Valentine leukocidin toxin (PVL) by the multiplex PCR technique. The antibiotic susceptibility profile for MRSA strains was realized by automatized methods and for MSSA strains it was used Kirby Bauver. 66 samples were confirmed as S. aureus by PCR. The prevalence of MRSA was 7.5% and 33.8% of MSSA. The 66% of the strains were isolated from raw ground beef and the 34% of pork chop meat. The isolations presented about 2 – 12% of multi-resistance to the antibiotics used. The MRSA showed resistance to amoxicillin- clavulanate (57%), ampicillin-sulbactam and cefazolin (85%), erythromycin and clindamycin (7%), tetracycline (35%). The 10% of the isolated strains had the gen of PVL toxin and the 71% of those were identified in samples of raw pork meat and the 28% in raw ground beef. This study reports for the first time, how meat raw products commercialized in the city of Cartagena could build a dissemination source of MRSA carrier of PVL toxin that could generate a public health disease.